(3JShjI GdefGRYGJ GdEOGQjI hOjkG ai VhA OSJhQ (B2014/ s - (3CMeO EHQGgje eMeO ecis; (3UHQi eMeO GdSfhSis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3dG Tc Gf GdefGRYI GdEOGQjI JeKd GdhSjdI GdJi cadgG GdeTQY ddCTNGU dMeGjI Mbhbge ai ehGLgI GdEOGQI(B: (3EdG Cfg fXQG dcKQI GdbVGjG h HWA GdJbGVi OaYJ GdeTQY Gdi JHfi hSGFd HOjdI(B: (3dYd GgegG(B: (3GdfXe GdGOGQi(B: (3GdUdM(B: (3GdJhajb(B: (3GdJMcje(B: (3GdJShjI GdhOjI(B. (3h JQei GdJShjI GdhOjI ddefGRYI GdGOGQjI Gdi GfgGA GdfRGY HQVGA WQajg ai eQMdI JMVjQ GdOYhi GdGOGQjI CeGe gjFI eahVi GdOhdI(B: (3h Ohf GdGSJeQGQ ai GLQGAGJ(B: (3h Pdc ai VhA GdeHGOF GdbGfhfjI GdJi bQQJgG GdeMceI GdGOGQjI GdYdjG(B: (3WHbG ddeGOI (B(28) (3ef bGfhf eLdS GdOhdI Qbe (B(47) (3dSfI (B1972: (3aEf JeJ GdJShjI CKHJJ ai eMVQ jhbY ef GdNUhe Ch hcdGFge h jchf ddeMVQ bhI GdSfO GdJfajPi h JYWi UhQJg habG ddbhGYO GdebQQI ddCMcGes
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B172-179s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdefGRYGJ GdEOGQjI s; (3JShjI GdefGRYGJ GdEOGQjI hOjkG s; (3OSJhQ (B2014s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes